Wood 14C Dating with AixMICADAS: Methods and Application to Tree-Ring Sequences from the Younger Dryas Event in the Southern French Alps. Issue 1 (18th September 2017) - Capano, Manuela; Miramont, Cécile; Guibal, Frédéric; Kromer, Bernd; Tuna, Thibaut; Fagault, Yoann; Bard, Edouard
Abstract: The AixMICADAS facility is in part dedicated to research on radiocarbon ( 14 C) calibration by means of various archives. For this purpose, we are improving upon the capacity to accurately date subfossil wood. In the current study, nine chemical pretreatment protocols are tested on six wood samples of known ages. The optimization based on 14 C ages, 13 C/ 12 C ratios, carbon % and overall mass yield % leads us to favor the acid-base-acid-bleaching pretreatment (ABA-B). This efficient method is shown to provide a residue of holocellulose with optimal blanks equivalent to an age of 51, 300 14 C BP with a standard deviation of 1500 yr based on 25 analyses. The seven wood samples from the Sixth International Radiocarbon Intercomparison (SIRI) are then analyzed as a further verification of the accuracy of our method. As a first scientific contribution, we studied two tree-ring sequences from subfossil pines (Barb12 and Barb17) collected in the southern French Alps. New 14 C analyses were performed at high resolution (every third year) and are shown to agree well with results obtained previously by high precision β-counting on CO2 from large samples at lower resolution for Barb17 and accelerator mass spectrometry (AMS) data for Barb12. The new 14 C series are then matched to the Kauri and YDB chronologies: the new sequence of Barb12-17 tentatively corresponds to the interval between 12, 836 and 12, 594 cal BP within the Younger Dryas cold period. The 14 C comparison between the Barb12-17 sequence from France and the Kauri sequence from New Zealand allows calculating the 14 C Inter-Hemispheric Gradient (IHG), with an average value of ca. 57 yr. The IHG stayed relatively high throughout the studied period. Interestingly, the IHG exhibits a transient maximum value (ca. 100 yr) during the period of rapid Δ 14 C rise (12, 750–12, 720 cal BP), a behavior that could be due to a delayed response of the Southern Hemisphere.